LGG-09. SENOLYTIC AGENT NAVITOCLAX TARGETS VINBLASTINE- AND MAPK INHIBITORS-INDUCED SENESCENT TUMOUR CELLS IN PAEDIATRIC LOW GRADE GLIOMAS. (1st June 2021) - Guiho, Romain; Selt, Florian; Stone, Thomas; Jacques, Thomas; Hargrave, Darren; Gil, Jesús; Witt, Olaf; Milde, Till; Barbera, Juan Pedro Martinez
Abstract: Pilocytic astrocytoma (PA, WHO grade I), the most common paediatric brain tumour, is characterized by constitutive activation of the MAPK pathway. PA tumours show a slow growth, without tendency to progress to high-grade malignancies. However, a significant group of patients for whom a total resection is not feasible require additional therapy. The typical proliferative index of a PA, measured by Ki-67 staining, is 1–2%, whereas a large part of the tumour is Ki-67 negative and expresses markers of oncogene-induced senescence (OIS) such as SA-β-Gal positivity and the cell cycle inhibitors p16 INK4a (CDKN2A) and p21 Cip1 (CDKN1A). Conventional treatments (i.e. chemotherapy) tend to target only proliferative cells and the effect of new molecularly targeted therapies (e.g., MAPK pathway inhibitors) on senescent cells remains unclear. Here, we discuss the opportunities to combine these therapies with new compounds targeting the senescent cells, referred to as senolytics, using three different PA models. (1) Ex vivo culture of human PA tumours (2) Two cell lines: the DKFZ-BT66 PA human cell line, carrying the oncogenic driver KIAA1549:BRAF-fusion, used as a model of OIS; and the proliferative BT40 cell line harbouring the BRAF V600E mutation; (3) In vivo xenograft model induced by orthotopic transplantation of BT40 cells. We have previously shown that OIS cells exhibit an increased sensitivity to senolytic compounds, such as navitoclax, a clinically approved BCL2/XL inhibitor, relative to proliferative controls (Buhl et al, Clin Cancer Res. 2019 ). Our current research demonstrates that treatments with low doses of chemotherapy (e.g., vinblastine) or MAPK inhibitors (e.g., dabrafenib or trametinib) triggers a therapy-induced senescence response in proliferative cells (e.g., abolished proliferation, SA-β-Gal positivity, SASP production), making these senescent cells sensitive to senolytic compounds, including navitoclax. Together, our research provides a strong rationale supporting the combined use of senolytics with current conventional and targeted therapies against human PA.